How accounting systems and information quality affect financial performance in Iraqi banks: The role of financial information reliability - Abdulkareem Abdulghani Oudah; Yusra Hadi Ibrahim; Abdulhasan Rahim Hamadi (Heritage and Sustainable Development)
This investigation aims to understand the relationship between accounting information systems and financial performance in Iraqi banks, as well as exploring the indirect effects of effect of these systems on financial performance in Iraqi banks and the quality of their accounting information. The authors developed a new method of building called AIS-enabled SEM that has been previously experimented with by scholars and professionals. It is derived from a body of research regarding the accounting information system and quality. Iraqi banks that operated in the commercial sector collected data via convenience samples. Through personal relationships, the authors gained contact with participants in all of the Iraqi financial institutions. Additionally, the process of collecting data took 65 days, which began on January 1st and March 5th, 2024. 12 Iraqi banks participated in the final sample of 261 respondents, via the questionnaire, and were analyzed via structural equation modeling with partial least squares using SmartPLS 4 software that satisfies the criteria for a sample of size 4 [54]. The results demonstrated that accounting information systems, the quality of accounting information systems, and the dependability of financial information have a positive and significant indirect effect on the financial performance of Iraqi banks. The results also demonstrated that the quality of the accounting information systems and the volume of the accounting information systems have an effect on the financial performance of Iraqi banks that rely on the reliability of financial information to conduct business.